Development of a novel experimental rat model for brachial plexus avulsion injury. Issue 9 (17th June 2015) - Yang, Jiantao; Li, Xiangming; Hou, Yi; Yang, Yi; Qin, Bengang; Fu, Guo; Qi, Jian; Zhu, Qingtang; Liu, Xiaolin; Gu, Liqiang
Abstract : Brachial plexus injuries (BPI) are devastating events that frequently result in severe functional impairment of the upper extremity, and yet, present surgical reconstruction provides limited results. An animal model is an important tool to study peripheral nerve repair and regeneration. Here, a passive traction apparatus that allowed a multidirectional force exerted on a fixed forelimb was designed to produce a BPI rat model in a noninvasive manner. Behavioral and histological analyses were carried out to assess the suitability of the model. Using the apparatus, a reproducible upper BPI model was established with the forelimb abducted 30° and a test weight of 2 kg. Avulsion of the nerve roots resulted in almost a total loss of forelimb function and the average Terzis score was decreased significantly compared with the sham group. No obvious recovery of shoulder and elbow movements was noted during the test period. In addition, nerve roots avulsion injury led to severe retrograde degeneration of motoneurons in the C5-C7 spinal cord segments. Nissl staining results showed that motoneurons decreased significantly in number and appeared to have irregular morphologies. These results indicated that a novel noninvasive rat model for BPI that simulates the mechanism of a human lesion could be produced using our passive traction apparatus, and it is expected to produce reliable preclinical evidence in the assessment of new therapeutic strategies for this lesion.